Geophysical Hazards Minimizing Risk, Maximizing Awareness - Beer, Tom (International Year of Planet Earth, 2010)
This volume, written by the Hazards Science Team of the International Year of Planet Earth, brings together some of the most influential international scientists dealing with Natural Hazards and society's response to natural hazards. It recognises that hazards, like poverty, will always be with us but that concerted and organised societal response can prevent a hazard becoming a disaster. By bringing together geoscientists, social scientists and those concerned with the administration of international science and international disaster reduction, this book details the state-of-the-science as well as the state-of-the-response in natural hazards. The contents of this volume fall into four parts: Part 1 deals with the IYPE Hazards Theme and its relation to society, emphasising that implementation of the Hyogo Framework for Action requires a strong emphasis on human societies, human security, and that this can be achieved only through appropriate communication. Part 2 focuses on the response of the international scientific community. Part 3 concentrates on geophysical risk and sustainability by considering climate and climate change as well as the theory and the praxis involved in hazards, their prevention and mitigation. Part 4 relates to the observation and assessment of geo-hazards and risk.